The Process‐Oriented Understanding on the Reduced Double‐ITCZ Bias in the High‐Resolution CESM1 - Enze Dong; Fengfei Song; Lixin Wu; Lu Dong; Shengpeng Wang; Fukai Liu; Hong Wang (Geophysical Research Letters)
Abstract The double‐Intertropical Convergence Zone (ITCZ) bias is a common model bias, which has puzzled the climate model community for several decades. Here, by comparing a high‐ and low‐resolution state‐of‐the‐art model CESM1, it is found that the double‐ITCZ bias is largely reduced in the high‐resolution CESM1. The key reason is the realistic colder sea surface temperature (SST) over the southeast Pacific (SEP) in the high‐resolution model. This realistic SEP SST is mainly due to a spuriously deeper mixed layer with a more realistic wind, as the sensitivity of mixed layer depth to wind is overestimated in both versions of CESM1. The better representation of terrain, such as Andes Mountains, elevates warm advection from inland to the coastal region, which maintains the inversion structure favorable for low cloud. The resultant increased coastal cloud in the high‐resolution CESM1 causes the colder coastal SST, thus improving the wind and deepening the mixed layer.